Students’ Accuracy In Pronouncing English Palate Alveolar Sounds /ꭍ/ - B, Lumoindong (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study explores the accuracy of students in pronouncing English palate-alveolar sounds, with a specific focus on the "ꭍ" sound, which is prevalent in numerous English words and can be challenging for non-native speakers. This study aims at identifying some common pronunciation errors among learners, understand the underlying causes, and propose strategies for improvement. The research involved a diverse group of students from varying linguistic backgrounds, analyzing their pronunciation through recorded speech samples and targeted pronunciation tasks. The results indicated that a significant number of students exhibited difficulty with the "ꭍ" sound, often substituting it with other similar-sounding phonemes or distorting its articulation. Factors contributing to these pronunciation challenges were identified, including native language interference, limited exposure to authentic English sounds, and lack of focused pronunciation training. The study underscores the importance of specialized pronunciation instruction, incorporating phonetic exercises and visual aids to enhance learning.